1994
DOI: 10.1111/j.1432-1033.1994.tb20008.x
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide that Stimulates Phosphorylation of the Plant Insulin‐Binding Protein

Abstract: The soybean seed basic 7 s globulin (Bg) is capable of binding bovine insulin and insulin-like growth factors, and has protein kinase activity which corresponds to about two thirds of the tyrosine kinase activity of the rat insulin receptor. A 4-kDa peptide named leginsulin, which can bind to Bg and compete with insulin for binding to Bg, was isolated from radicles of germinated soybean seeds. The leginsulin had a stimulatory effect on the phosphorylation activity of Bg, suggesting that it is involved in cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 15 publications
2
88
0
2
Order By: Relevance
“…PA1b is the smaller of two unrelated PA1 subunits that are not associated with each other in vivo. Soybean leginsulin is homologous to PA1b and can compete with insulin for binding to an insulin-binding protein (Watanabe et al, 1994). There is no evidence that leginsulin is a plant peptide hormone, but it may be part of a signal transduction pathway involving phosphorylation.…”
Section: Does Modifying Nutritionally Important Compounds Have Conseqmentioning
confidence: 99%
“…PA1b is the smaller of two unrelated PA1 subunits that are not associated with each other in vivo. Soybean leginsulin is homologous to PA1b and can compete with insulin for binding to an insulin-binding protein (Watanabe et al, 1994). There is no evidence that leginsulin is a plant peptide hormone, but it may be part of a signal transduction pathway involving phosphorylation.…”
Section: Does Modifying Nutritionally Important Compounds Have Conseqmentioning
confidence: 99%
“…This protein was shown to have protein kinase activity suggesting that it might be a component of a signaling cascade in which insulin or a related molecule is present. In Watanabe et al (1994) isolated a 4 kDa peptide from soybeans has similar signaling mechanism as that of IGF but its sequence was found to be different from insulin and IGF and named it leginsulin, further experiment through Western-blotting showed its presence in adzuki and mung beans and carrot (Watanabe et al, 1994). Following this suggestion Ilgoutz et al (1997) demonstrated transcription of a leginsulin gene in developing lupin cotyledons.…”
Section: Herbal Insulin: Other Than Pancreasmentioning
confidence: 98%
“…20) DGP is rich in peptides and amino acids, and hence its fertile effect on B. rapa was investigated. B. rapa was grown with either chemical fertilizer or DGP for 28 d, then the final fresh weights were measured (Table 3).…”
Section: Analysis Of Bluegill Degradation By Strain Bgm1mentioning
confidence: 99%